The Role of The Inclusion Class Teacher in Guidance and Counseling for Child with Special Needed (Case Study at Islamic SDI Aisyah, Jatinom Blitar) - Budi Pranoto; Muallifah (JARES (Journal of Academic Research and Sciences), 2022)
This study aims to determine how the role of inclusive classroom teachers in the implementation of counseling guidance. This research method uses a qualitative case study approach by collecting information data sourced from interviews and observations. Furthermore, the data is analyzed, and draw conclusions. The results of this study can be concluded that the role of teachers in inclusive classes in providing counseling guidance is very large even though the teacher feels that they do not have sufficient competence to carry out this role. Teachers improve their competence by participating in various trainings and self-development related to children with special needs.